Farm Machinery in Rural Rio de la Plata Region during the First Globalization. An Analysis of Spatial Heterogeneity (Uruguay and Argentina, 1880-1916) (Quinto Sol, 2023)
This paper studies the mechanization of agriculture in the rural regions of the Rio de la Plata during the First Globalization (1880-1916). Uruguay and Argentina developed an important growth and diversification of their agricultural production during this period. This growth accompanied the great livestock dynamism that both economies had achieved since the first decades of the 19th century. We analyze the process by dispensing national approaches. A geo-referenced database is constructed at a micro-regional level to identify the location of the main agricultural production areas and to trace their evolution throughout the period. A clustering analysis is also carried out to explore the spatial heterogeneity that characterized the River Plate agriculture and provide elements for its interpretation.
Keywords: River Plate agriculture; mechanization; first globalization